Extended linear programming in models of location of concrete mix production plants - Kozniewski, Edwin; Orlowski, Zygmunt (Journal of Civil Engineering and Management, 2005)
The paper discusses the location problem of production plants exemplified by concrete mix production plants (Ist model), taking into consideration the demand variability in time (IInd model), and the analytical method of the localization of industrial plant with a considerable amount of transportation costs of concrete mix and concrete aggregate (IIIrd model). Changes in demand for concrete mix in time t lead to changes in plants’ location. Assuming that there exist concrete mix production plants, one should make a simulation of demand for concrete mix which occurs at the time t The presented models are the essential generalisation of the problem discussed in the earlier papers. The matrix of construction costs must be always defined as a four‐dimensions vector (the set of four values): the production plant construction cost, the cost of plant’s modernisation (which is the result of changing demand for concrete mix), the cost of liquidation (dismantling) of a production plant or the cost of moving of an existing production plant. Three new generalised notions concerning the classical linear programming (mixed programming, mixed programming with time and two‐optimised conjugate linear system) have been introduced. The algorithms describing the above‐mentioned models of location changes were suggested, and programmes solving the location problems were prepared in PASCAL. Išplėstinis betono gamyklų išdėstymo tiesinio programavimo modelis Santrauka. Aptariama gamyklų išdėstymo problema iliustruota betono gamyklų pavyzdžiu. I modelyje nagrinėjamas betono gamyklos išdėstymas nepriklausomai nuo betono poreikio kitimo laikui bėgant. II modelyje įvertinamas betono poreikio kitimas laikui bėgant. III analiziniame pramonės gamyklų išdėstymo modelyje įvertintos betono mišinio bei užpildo transportavimo išlaidos. Kintant betono poreikiui laikui bėgant, kinta ir gamyklų išdėstymas. Esamoms betono gamykloms turi būti atliktas betono mišinio poreikio kitimo laikui bėgant modeliavimas. Pateikti modeliai apibendrina ankstesniuose straipsniuose suformuluotas esmines problemas. Statybos išlaidų matrica turi būti sudaryta kaip keturių dimensijų vektorius (keturių reikšmių aibė): gamyklos statybos išlaidos, gamyklų modernizavimo išlaidos, kurias lemia betono poreikio kitimas, gamyklos likvidavimo išlaidos arba esamos gamyklos perkėlimo išlaidos. Pateiktos trys naujos apibendrintos metodikos, susijusios su klasikiniu tiesiniu programavimu (mišrusis programavimas, mišrusis programavimas laikui bėgant ir pagal du požymius optimizuota jungtinė tiesinė sistema). Pasiūlyti išdėstymo modelių aprašymo algoritmai, kurių sprendimams parengtos kompiuterinės programos PASCAL programavimo kalba. Reikšminiai žodžiai: proceso modeliavimas, išdėstymo problema, transportavimo metodas, betono mišinys, tiesinis programavimas, mišrusis programavimas, jungtinis programavimas. First Published Online: 14 Oct 2010